2010
DOI: 10.1002/prop.201000016
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic helicity conservation in SUSY

Abstract: We summarize the extensive work started in [1], according to which total helicity is conserved for any two‐to‐two process, at sqrt s >> MSUSY and fixed angles, in any SUSY extension of SM. Asymptotically the theorem is exact. But it may also have important implications at lower energies . Up to now, these have been investigated to 1loop electroweak (EW) order for the processes ; as well as the 17 gg → HH', and the 9 gg → VH processes, where H,H' denote Higgs or Goldstone bosons, and V = Z, W±.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…of (9) is of course determined by (6), and similar expressions for the other gauge bosons. As seen in (9), most of the gauge and gaugino asymptotic amplitudes, are identical. But for µ −τ = ±1, sign differences appear, related to the way the fermionic states in the l.h.s.…”
Section: Supersimplicity For Gg → V Vmentioning
confidence: 67%
See 2 more Smart Citations
“…of (9) is of course determined by (6), and similar expressions for the other gauge bosons. As seen in (9), most of the gauge and gaugino asymptotic amplitudes, are identical. But for µ −τ = ±1, sign differences appear, related to the way the fermionic states in the l.h.s.…”
Section: Supersimplicity For Gg → V Vmentioning
confidence: 67%
“…Results analogous to (9), are also true for longitudinal vector bosons, which necessarily include higgsino amplitudes in the l.h.s. [13,10,14].…”
Section: Supersimplicity For Gg → V Vmentioning
confidence: 95%
See 1 more Smart Citation
“…In such detail calculations, we have observed that in processes involving external gauge bosons, huge cancelations among the various diagrams need to conspire, in order to establish HCns [1,2,3]. On the contrary, no such cancelations appear, in processes where all external particles are fermions or scalars.…”
Section: Introductionmentioning
confidence: 99%